Viral diseases on apple in southern Syria - Houda Z. Kawas (مجلة مركز بحوث التقنيات الاحيائية, 2012)
108 sample Collected from the fields of farmers in the areas of apple cultivation in the south of Syria during the years 1998-2007, and the most important symptoms associated with infection were recorded, results of the biometric tests (mechanical inoculation on indicator plant) and examination by electron microscope and serological tests (ELISA) using antisera of Apple mosaic virus, Apple chlorotic leaf spot virus, Tomato ring spot virus , Tomato spotted wilt virus, Tobacco ring spot virus , Tomato black ring virus and Arabis mosaic virus to the spread of a virus infection of Apple chlorotic leaf spot virus (ACLSV) by 24%, Apple mosaic virus (ApMV) by 26.9% and to register cases Tomato ring spot virus (TomRSV) by 13% and Tobacco ring spot virus (TRSV) by %14.8, Tomato black ring virus (TBRV) rate of % 12.03 and Arabis mosaic virus (ArMV) 2.43% for the first time on apples in Syria, and the likelihood of several viral and viroid diseases, that we need to reassess the health situation in view of the importance of maintaining the cultivation of apples and recommended program documentation for the production of propagation of disease-free, with proposal to use molecular methods to detect and identify viral diseases causes and strains prevalent in Syria.